2020
DOI: 10.3390/s20020526
|View full text |Cite
|
Sign up to set email alerts
|

LPI Radar Waveform Recognition Based on Features from Multiple Images

Abstract: Detecting and classifying the modulation type of the intercepted noisy LPI (low probability of intercept) radar signals in real-time is a necessary survival technique in the electronic intelligence systems. Most radar signals have been designed to have LPI properties; therefore, the LPI radar waveform recognition technique (LWRT) has recently gained increasing attention. In this paper, we propose a multiple feature images joint decision (MFIJD) model with two different feature extraction structures that fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Previous research [ 18 ] found that, even if the network performance is good enough (it means that the network's recognition accuracy rate of the trained dataset had reached to a high level and the recognition accuracy rate to most of the waveforms can reach 99%), there are still some signals that are easily confused. The similarity between the waveforms is high (or the similarity between the converted time-frequency images is high) and the difference of the extracted features is not obvious.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [ 18 ] found that, even if the network performance is good enough (it means that the network's recognition accuracy rate of the trained dataset had reached to a high level and the recognition accuracy rate to most of the waveforms can reach 99%), there are still some signals that are easily confused. The similarity between the waveforms is high (or the similarity between the converted time-frequency images is high) and the difference of the extracted features is not obvious.…”
Section: Methodsmentioning
confidence: 99%
“…In [31], a 7-layer CNN along with a novel tree structure-based process optimization tool (TPOT) classifier was designed. In [32], Ma et al employed two different DNN structures to approach the waveform classification problem: a 11-layer CNN and a bidirectional LSTM, with the former exhibiting better performance. In [33], transfer learning was employed to counter the problem of limited training data.…”
Section: A DL For Lpi Radarmentioning
confidence: 99%
“…The most common classifiers in radar AMC algorithms are hierarchical decision trees and artificial neural networks, whereas there are a lot of possible signal features, including those derived from instantaneous signal properties [ 4 , 5 , 6 ], higher-order statistics [ 6 , 7 , 8 ], time-frequency distributions (TFDs) [ 8 , 9 , 10 ] or power spectral density [ 11 , 12 ]. Over the recent years, one can notice an increasing number of deep learning AMC algorithms, especially those using time-frequency image features combined with a convolutional neural network classifier [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%